The innovation process and network activities of manufacturing firms: Conceptual considerations and empirical evidence from the metropolitan region of Vienna - Manfred M. Fischer (European Regional Science Association (ERSA), 1998)
Innovation networks of manufacturers are currently receiving much attention as a competitive strategy. The contribution represents a response to the growing recognition that there are very important reasons why we need a better understanding of the relationship between innovation and networking. This response is conceptual in form, but enriched with some empirical evidence from the metropolitan region of Vienna. The paper demonstrates unambiguously the importance of external network activities during the innovation process that are organized around five types of networks: customer networks, manufacturing supplier networks, producer service supplier networks, producer networks and co-operation with research institutions and departments of universities. The data clearly indicate that networking is not only and primarily a metropolitan phenomenon. Spatial proximity is just one, but evidently not the decisive criterion for innovation-oriented relationships. The geography of networking largely extends to national and international levels.
Keywords: 330